The Role of Problem Based Learning on Improving Students’ Mathematical Critical Thinking Ability and Self-Regulated Learning - Retnaningsih, Musriana; Sugandi, Asep Ikin (IKIP Siliwangi, 2018)
This study is a pre test-post test experimental control group design having a goal to analyze the role of problem based learning on students’ mathematical critical thinking ability and self regulated learning. The study involved 60 eighth grade students of an MTs, a mathematical critical thinkng test, and a mathematical self regulated learning scale. The study found that on mathematical critical thinking ability, its gain, and on mathematical self regulated learning, students getting treatment with problem based learning approach attained better grade than that of students taught by conventional teaching. The first group students obtained at fairly good grades level, while the students taught by conventional teaching attained at medium grades level. The other findings, there was fairly good association between mathematical critical thinking ability and mathematical self regulated learning.